Faster Parameterized Algorithm for Cluster Vertex Deletion - Tsur, Dekel (Theory of computing systems, 2021)
In the Cluster Vertex Deletion problem the input is a graph G and an integer k . The goal is to decide whether there is a set of vertices S of size at most k such that the deletion of the vertices of S from G results in a graph in which every connected component is a clique. We give an algorithm for Cluster Vertex Deletion whose running time is O ∗ (1.811 k ).